Masked Hypertension Defined by Home Blood Pressure Monitoring Is Associated With Impaired Flow‐Mediated Vasodilatation in Patients With Cardiovascular Risk Factors. Issue 9 (25th June 2013) - Kabutoya, Tomoyuki; Hoshide, Satoshi; Ogata, Yukiyo; Eguchi, Kazuo; Kario, Kazuomi
Abstract : The relationships between home blood pressure (BP), masked hypertension defined by home BP, and integrated flow‐mediated vasodilation (FMD) response remain unclear. The authors enrolled 257 patients (mean age, 63.5 years; 51% men) who had at least one cardiovascular risk factor. FMD of the brachial artery was measured with a semiautomatic edge‐detection algorithm. The integrated FMD response was calculated as the area under the dilation curve during 120 seconds after deflation (FMD‐AUC120 ) and the FMD magnitude as the percentage change in peak diameter (ΔFMD). Masked hypertension was defined by office BP <140/90 mm Hg and home BP ≥135 mm Hg and/or 85 mm Hg. Home systolic BP was inversely correlated with FMD‐AUC120 and ΔFMD (FMD‐AUC120 : r =−.23, P <.001; ΔFMD: r =−.13, P =.041), and office systolic BP was inversely associated with FMD‐AUC120 ( r =−.16, P =.011), but not with ΔFMD. After adjusting for covariates, home systolic BP (β=−.27, P =.003), but not office BP, was inversely associated with FMD‐AUC120, whereas ΔFMD was not associated with office or home systolic BP. FMD‐AUC120 was significantly lower in patients with masked hypertension compared with those with normotension (7.7±6.7 vs 11.5±8.8 mm × s, P =.048). Home systolic BP and masked hypertension defined by home BP were associated with a decrease in FMD‐AUC120 .